Utilidad del pcl-r como instrumento de evaluación en pacientes con trastornos mentales - Farez Zambrano, Jenny Fergie (Machala : Universidad Técnica de Machala, 2022)
Introduction: Psychopathy could be understood within individuals who maintain an average or superior intellectual capacity, but who present persistent criminal behavior, where there is no respect for legal, social or moral norms, but who has the capacity to engage in an emotional or social relationship with others. In the legal and forensic field, psychopathy is characterized as the individual who breaks the law or established norms in a geographic region. Objective: To establish the usefulness of the PCL - R in patients with mental disorders, through the analysis of articles of high impact in health, with the purpose of its applicability in the clinical - psychiatric field. Methodology: A descriptive study based on a systematic literature review of different scientific articles of evidence-based medicine, from multiple digital repositories of high impact in health (Scopus, Pubmed, Taylor and Francis, Elsevier, Cochrane) of the last 5 years in progress, and literature on legal and forensic medicine. Conclusion: The PCL-R is a test that is applied to the individual to be investigated with a tendency to psychopathic personality, which allows evaluating the clinical and forensic conditions of psychopathy, in relation to social deviance disorders, assessing the personality of the individual. In Ecuador, this test should be applied to the subjects of the penitentiary system; to establish their behavior or psychopathic personality, and to be able to apply appropriate judicial and health regulations for this population and to have an integral recovery of quality of the individuals of the national penitentiary system.
Introducción: La psicopatía podría comprenderse dentro de los individuos que mantienen una capacidad intelectual media o superior, pero que presentan una conducta delictiva persistente, en donde no se respeta las normas legales, sociales o morales, pero que tiene la capacidad de entablar una relación emocional o social con los demás. En el ámbito legal y forense, la psicopatía se protagoniza como el individuo que incumple la ley establecida en una región geográfica. Objetivo: Establecer la utilidad del PCL – R en los pacientes con trastornos mentales, a través del análisis de artículos de alto impacto en salud, con la finalidad de su aplicabilidad en el ámbito clínico – psiquiátrico. Metodología: Un estudio descriptivo basado en una revisión sistemática bibliográfica de diferentes artículos científicos de medicina basada en evidencia, de múltiples repositorios digitales de alto impacto en salud (Scopus, Pubmed, Elsevier, Cochrane) de los últimos 5 años en curso, y literatura sobre medicina legal y forense. Conclusión: PCL – R un test que se aplica al individuo a investigar con tendencia a la personalidad psicópata, que permite evaluar las condiciones clínicas, como forenses de la psicopatía, en relación con trastornos de desviación social, evaluando a grandes rasgos la personalidad del individuo. En el Ecuador se debería aplicar dicho test en los sujetos del sistema penitenciario; para establecer su conducta o personalidad psicópata, y poder aplicar normativas judiciales y salubristas adecuadas para esta población y tener una recuperación integral de calidad de los individuos del sistema penitenciario nacional.
Keywords: PSIQUIATRÍA; TRASTORNO MENTAL; TRASTORNO DE PERSONALIDAD ANTISOCIAL; SALUD MENTAL